Psychological processes in chronic pain: a structural model - Knotek, Petr; Knotková, Helena (Journal of pain management, 2008)
Several models of psychological processes in chronic pain have been developed in recent years. However, each of those models has numerous limitations and none of the existing model reflects the following processes observed in clinical practice in patients with chronic pain: 1) Pain in its acute sensory stage emerges in, different psychological conditions, including different experience of pain, pain beliefs and expectations; 2) affective processes change from the affective component of pain, fromt fear to generalized negative affects; 3) cognitive processing of pain changes from the observation of pain to self-perception changes. Objectives: We aimed to develop and test a model that would better reflect psychological changes associated with pain processing in patients with chronic pain. Methods: The initial hypothetical model representing stages of psychological changes associated with chronic pain included 9 factors operationalized with the total of 24 variables. The model was tested using the program EQS in 174 patients (71 M, 103 F) with non-malignant chronic pain of mean duration of 11.18 years, who responded to the set of 10 questionnaires and 3 rating scales. Results: Five variables that decreased correspondence of the model to the data were excluded. The final solution of the model with 19 variables supports the initial postulate of consecutive stages in processing of pain. The final solution confirmed that not only the initial acute pain itself but also patient’s pain beliefs can trigger cognitive and affective changes in pain processing.
Keywords: chronická nemoc; Humans; Models, Psychological; Psychological Phenomena; Chronic Disease; Pain; bolest; psychologické jevy a procesy; lidé; psychologické modely